Completing the SME carbon profile: scalable prediction of scope 3 emissions - Alec Phillpotts; Anne Owen; Jonathan Norman; Anna Trendl; John Gathergood; Norbert Jobst; David Leake (Journal of Industrial Ecology, 2026)
Despite growing recognition of significance, a business’s Scope 3 emissions remain rarely measured and as a result are poorly understood. This situation is particularly common amongst small and medium-sized enterprises (SMEs), which face additional obstacles to emission measurement. With this paper, we present a transaction-based approach to facilitate SME Scope 3 engagement. Using financial transaction data for 150,000 + UK SMEs, we produce spend-based Scope 3 estimates across key Greenhouse Gas Protocol categories. We then fit a series of hierarchical regression models to both quantify and identify firm-level Scope 3 emissions, with minimal user inputs. We find that this approach is effective in predicting the upstream emissions of both purchased goods & services (RSQ = 0.87) and fuel and energy-related activities (RSQ = 0.89 and 0.72), whilst weaker for more targeted categories such as business travel. We also find a small number of recurrent industry hotspots tend to account for 75% of a firm’s upstream emissions. By leveraging objective, standardised data to estimate emissions, this method provides a low-input alternative to costly micro-studies for generating Scope 3 insights, extending the visibility of emissions beyond a firm’s direct operations, revealing emission hotspots and supporting the development of value chain decarbonisation strategies.

Bridging the SME reporting gap: A new model for predicting Scope 1 and 2 emissions - Alec Phillpotts; Anne Owen; Jonathan Norman; Anna Trendl; John Gathergood; Norbert Jobst; David Leake (Journal of Industrial Ecology, 2025)
We present a novel statistical model for predicting Scope 1 and 2 emissions for small and medium‐sized enterprises (SMEs). Trained on financial transaction data from over 100,000 UK SMEs, the model targets a business segment excluded from formal emissions reporting and often under‐engaged in sustainability efforts. By leveraging scalable, objective data, our approach offers an accessible alternative to existing methods that rely on either coarse sectoral averages or detailed, resource‐intensive firm‐level activity data. In developing the model, we evaluate a range of predictors and find that incorporating industry‐level variables beyond basic emission intensity significantly enhances predictive accuracy. We also observe diminishing returns from additional model complexity, reinforcing the value of a parsimonious, low‐input design. The final model achieves RSQ values of 0.89 for Scope 1 and 0.72 for Scope 2, improves accuracy by up to 50% compared to sector‐level estimates, and performs reliably on out‐of‐sample data. Our findings provide a simpler approach to emissions estimation for SMEs, supporting broader climate engagement among smaller actors.

Targeting carbon reduction in UK households: A new segmentation model using financial transaction data - Jasmine Wells; Anna Trendl; Anne Owen; John Barrett; Norbert Jobst; David Leake (Journal of Industrial Ecology, 2025)
Designing effective and targeted policies to reduce household emissions needs to consider variability in household consumption patterns, preferences, and financial capacities. This paper introduces a new segmentation model of household carbon footprints that uses financial transaction data from over 700,000 customers of a major high‐street bank. Our approach considers socioeconomic, consumer‐preference, and spatial factors to identify 10 distinct household typologies. We focus on targeted retrofit as a practical application, identifying three high‐impact household types with the capacity to invest— “Suburban Home Improvers,” “Car and Tech Enthusiasts,” and “Affluent Families”— and suggest targeted policy and communication opportunities. Our segmentation supports a new data‐driven policy design that considers both the technical potential and diverse behavioral factors affecting decarbonization decisions.

Non-isothermal consolidation: A systematic evaluation of two implementations based on multiphase and Richards equations - Michael Pitz; Sonja Kaiser; Norbert Grunwald; Vinay Kumar; Jörg Buchwald; Wenqing Wang; Dmitri Naumov; Aqeel Afzal Chaudhry; Jobst Maßmann; Jan Thiedau; Olaf Kolditz; Thomas Nagel (International Journal of Rock Mechanics and Mining Sciences, 2023)